Biodiversity, land use change, and human health in northeastern Madagascar: an interdisciplinary study. (September 2019) - Kramer, Randall; Herrera, James; Fitzgerald, Ryan; Moody, James; Owens, Ajile; Pender, Michelle; Ravelomanantsoa, Ny Anjara Fifi; Regula, Lisa; Tortosa, Pablo; Nunn, Charles
Abstract: Background: Given rapid land use changes and climate change underway in many low-income and middle-income countries, it is vitally important to understand how ecosystem changes influence biodiversity and human health, and to identify actions that can improve conservation, while also improving human health. We are investigating how human activities alter ecological communities and influence infectious disease risk near Marojejy National Park in northeastern Madagascar. We are coupling (i) cutting-edge social science methods to investigate the drivers of human land-use decision-making, and (ii) ecological analyses to investigate how these land use decisions impact zoonotic infectious disease transmission in small mammals, domesticated animals, and humans. Methods: The study team conducted preliminary fieldwork in one village in 2017 and 2018 including household surveys, social network surveys and trapping of small mammals to screen for parasites and pathogens. We constructed a social network of 500 people to investigate disease risk patterns based on agricultural co-working relationships. In addition, the team captured 552 small mammals and found variation in abundance and diversity across a gradient of human land use. Findings: Results show that illness is frequent within community households, with a high prevalence of fevers over the previous 3 months (40%). Non-native species have higher relative and total abundance in agricultural fields, with highest relative abundance of introduced species in the unsustainable rice farming setting. Prevalence of Leptospira, a pathogenic bacterium transmitted through urine and contaminated water, was over four times higher in paddy rice fields than in forests or hillside slash-and-burn fields. Interpretation: Our findings are consistent with the hypothesis that changes in land use and biodiversity can influence animal health, which may in turn affect disease risk for humans. We are now expanding ecological and household data collection to additional villages, as well as developing choice experiments to better understand farmer decision making about sustainable agricultural practices. Funding: Duke University Bass Connections programme for interdisciplinary research.